Sinto and national heart of japanese people (Journal of Oriental Studies, 2018)
This article is dedicated to Sinto, its unique and harmonious coexistence with the other religions,such as Buddhism, Christianity and Confucianism. Considered the relationship between the governmentand Sinto and its use as the main ideological instrument. This article narrates the story, which tells, thatthroughout the history of the government in the most critical moment for the union of the nation and itsrevival of patriotic feelings, the authorities of the country utilised the main idea of Sinto – an idea abouta divine origin of the nation. The historical periods are described: the formation of the state, restorationMeiji, postwar Japan and the time of the phenomenal economical growth in the country